PENGARUH HEURISTIC BIASES TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI SAHAM (STUDI PADA INVESTOR SAHAM DI KOTA MATARAM) - Bimo Abdinegoro; Budi Santoso; Siti Aisyah Hidayati (LPSDI Bina Patria, 2023)
This research aims to analyze the Influence of Heuristic Bias: Stock Investors in Mataram City. This type of research is associative with quantitative methods. The population in this research is all investors in Mataram City. Sampling was carried out using a non-probability sampling technique with the quota sampling method. From the existing population, there are 101 (one hundred and one) investors who can be taken as samples. The data collection technique used in this research is by using a questionnaire. To achieve research objectives and hypothesis testing, the data obtained will be processed as needed using the GSCA (Generalized Structured Component Analysis) statistical tool. The research results show that heuristic bias (Representativeness, Availability, Anchoring, Overconfidence) has a positive and significant effect on investors' stock investment decisions in Mataram City. This is based on the age of the respondents who are of productive age, most of them are men, the education level of most of them is S1, the investment period is less than 1 (one) year. Recommendations can be aimed at: For investors and potential investors, it is hoped that they can provide information by considering the influence of bias in making appropriate decisions regarding their investments with the aim of minimizing investment risks and obtaining maximum returns